Avukatlar hakkında arama ve elkoyma - Tığlı, Dicle Erdoğmuş (İstanbul Kültür Üniversitesi / Lisansüstü Eğitim Enstitüsü / Kamu Hukuku Ana Bilim Dalı / Kamu Hukuku Bilim Dalı, 2021)
Tez çalışmamızda, 5271 sayılı Ceza Muhakemesi Kanunu'nda birinci kitap, dördüncü kısımda, koruma tedbirleri başlığı altında düzenlenen arama ve elkoyma tedbirleri ile avukatlar hakkında arama ve elkoyma tedbirinin uygulanması ele alınmıştır. Avukatlar hakkında arama ve elkoyma tedbirlerinin özel olarak düzenlenmesinin sebeplerinden sır saklama yükümlülüğü, avukatların bağımsızlığı, savunma hakkının korunmasına değinilmiş olup, bu kapsamda avukatların üstünün, konutlarının aranması ile bürolarında arama ve elkoyma, avukatın postasında elkoyma işlemi incelenmiştir. Çalışmamızın birinci bölümünde; avukatların kamu görevlisi olup olmadığı konusuna değinilerek, ceza muhakemesi işlemlerinden arama ve elkoyma tedbirlerinin avukatlar hakkında özel olarak düzenlenmesinin sebepleri incelenmiştir. İkinci bölümde; arama tedbiri, tedbirin avukatlar hakkında uygulanması, tedbirin denetimi ve hukuka aykırı olan arama işlemi ile bu durumdan kaynaklanan Devletin tazminat yükümlülüğü incelenmiştir. Üçüncü bölümde; elkoyma tedbiri, tedbirin avukatlar hakkında uygulanması, tedbirin denetimi ve hukuka aykırı olan elkoyma işlemi ile bu durumdan kaynaklanan Devletin tazminat yükümlülüğü, avukatlar hakkında uygulanan arama ve elkoyma tedbirlerinin hukuki denetimi ile Devletin tazminat yükümlülüğü incelenmiştir.

This thesis examines the measures of judicial search and seizure, and the execution of these measures in cases pertaining to lawyers, which have been regulated under the category of protection measures in the forth section of the first volume of the Turkish Criminal Procedure Code (Act No. 5271). In this regard, the principles of the lawyers' confidentiality obligation, the lawyers' autonomy, the protection of the right of defense are discussed as underlying reasons behind the specificity of the search and seizure measures pertaining to lawyers, and the practices of body search, search in the dwellings and search and seizure in the business places, seizure at the post office or during postal processes are examined. The first chapter of the thesis concentrates on the question of whether lawyers are to be considered to be public servants or not, and elaborates on the subsequent discussion on the underlying rationale of the particularity of the search and seizure measures pertaining to lawyers. The second chapter of the thesis elaborates on the measure of search and its execution in cases pertaining to lawyers, while also examining the mechanisms of its legal oversight, the cases of its unlawful execution and the state's obligation for compensation stemming from the unlawful execution of search measures. The third chapter of the thesis elaborates on the measure of seizure and its execution in cases pertaining to lawyers, the mechanisms of its legal oversight, the cases of its unlawful execution and the state's obligation for compensation stemming from the unlawful execution of seizure measures, while also examining the mechanisms of the legal oversight of the execution of the measures of search and seizure in cases pertaining to lawyers and the state's obligation for compensation.
Search and seizure measures pertaining to lawyers
Keywords: Hukuk; Arama; Law; Search